Erosion Prediction and Soil and Water Conservation Scenario Using The SWAT Model - Candra Dewi, Ni Luh Trisna; Sulastri, Ni Nyoman; Arya Arthawan, I Gusti Ketut; Ngadisih, Ngadisih (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Increasing population and development has resulted in inappropriate land use within watersheds that increase soil erosion. One of the hydrologic models that can be used to predict erosion and soil and water conservation in a watershed is SWAT. This research was conducted to predict erosion and the guidance of soil and water conservation in the Yeh Empas Watershed. This research was carried out in several stages, including data collection, data analysis and map validation using the ROC (receiver operating characteristic) and AUC (area under curve) methods. Results revealed that Yeh Empas Watershed had a very light EHL (erosion hazard level) category was found in the downstream area with an annual erosion value of 0 – 14.68 t/ha. In the middle area, the EHL was categorized as light with an erosion value of 15.44 – 57.22 t.ha-1.y-1. The upstream area has moderate EHL with a value of 65.20 – 178.64 t.ha-1.y-1. The validation of the EHL map using the ROC method showed a result of 0.83. This value was classified as very good. It can be concluded that SWAT predictions can be used in estimating erosion and soil and water conservation scenario to reduce 85% erosion. Keywords: Erosion prediction, Soil and water conservation scenario, SWAT models, Yeh Empas Watershed.